Faktor-faktor yang mempengaruhi kualitas laba pada perusahaan manufaktur - NATASHA SOLY; NOVIA WIJAYA (Jurnal Bisnis dan Akuntansi, 2017)
The purpose of the study is to get empirical evidence about factors that affect earnings quality of manufacturing listed company. Eight selected variables are board of directors, board size, managerial ownership, firm size, capital structure, liquidity, dividend payment, and profitability. Multiple regression method was applied on samples of 35 manufacturing listed companies that have been listed in Indonesia Stock Exchange (BEI) from period 2012 until 2015. Samples were selected based on purposive sampling method. The results showed that dividend payment and profitability had influence on earnings quality. Meanwhile, board of directors, board size, managerial ownership, firm size, capital structure, and liquidity had no effect on earnings quality.